(untitled) (Лучшие интеллектуальные исследования, 2025)
Thermal power plants (TPPs) convert the heat energy produced by burning fuel—such as coal, natural gas, or fuel oil—into mechanical and electrical energy. Their main components include a boiler, turbine, generator, and cooling system. This abstract examines the advantages and disadvantages of TPPs, their environmental impact, as well as opportunities for modernization and integration with alternative energy sources.